Answer:
the third one
Step-by-step explanation:
3)
(x/3)+(2/5)
(5x/15)+(6/15)
(5x+6)/15
4)
(2/x)+(3/7)
(14/7x)+(3x/7x)
(3x+14)/(7x)
5)
(x/2)+(1/3)+(x/4)
(6x/12)+(4/12)+(3x/12)
(9x+4)/12
Explanation: 3 x 2 + 10 x + 3 We can Split the Middle Term of this expression to factorise it. In this technique, if we have to factorise an expression like a x 2 + b x + c , we need to think of 2 numbers such that: N 1 ⋅ N 2 = a ⋅ c = 3 ⋅ 3 = 9 and, N 1 + N 2 = b = 10 After trying out a few numbers we get: N 1 = 9 and N 2 = 1 9 ⋅ 1 = 9 , and 9 + ( 1 ) = 10 3 x 2 + 10 x + 3 = 3 x 2 + 9 x + 1 x + 3 = 3 x ( x + 3 ) + 1 ( x + 3 ) ( 3 x + 1 ) ( x + 3 ) is the factorised form for the expression.
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
3
⋅
3
=
9
and,
N
1
+
N
2
=
b
=
10
After trying out a few numbers we get:
N
1
=
9
and
N
2
=
1
9
⋅
1
=
9
, and
9
+
(
1
)
=
10
3
x
2
+
10
x
+
3
=
3
x
2
+
9
x
+
1
x
+
3
=
3
x
(
x
+
3
)
+
1
(
x
+
3
)
(
3
x
+
1
)
(
x
+
3
)
is the factorised form for the expression.
Answer:
0.6604 m
Step-by-step explanation:
The convertion from inches to meters is 1 inch= 0.024 meters, so:
26 inches = 26 inch* 0.024 meters/inch = 0.6604 meters
Good luck!
Answer:
C. Exponential decay
Step-by-step explanation: